Radiologist agreement on the quantification of bronchiectasis by high-resolution computed tomography - Brito,Milene Carneiro Barbosa de (2017)
Abstract Objective: To evaluate radiologist agreement on the quantification of bronchiectasis by high-resolution computed tomography (HRCT). Materials and Methods: The HRCT scans of 43 patients with bronchiectasis were analyzed by two radiologists, who used a scoring system to grade the findings. Kappa (κ) values and overall agreement were calculated. Results: For the measurement and appearance of bronchiectasis, the interobserver agreement was moderate (κ = 0.45 and κ = 0.43, respectively), as was the intraobserver agreement (κ = 0.54 and κ = 0.47, respectively). Agreement on the presence of mucous plugging was fair, for central distribution (overall interobserver agreement of 68.3% and κ = 0.39 for intraobserver agreement) and for peripheral distribution (κ = 0.34 and κ = 0.35 for interobserver and intraobserver agreement, respectively). The agreement was also fair for peribronchial thickening (κ = 0.21 and κ = 0.30 for interobserver and intraobserver agreement, respectively). There was fair interobserver and intraobserver agreement on the detection of opacities (κ = 0.39 and 71.9%, respectively), ground-glass attenuation (64.3% and κ = 0.24, respectively), and cysts/bullae (κ = 0.47 and κ = 0.44, respectively). Qualitative analysis of the HRCT findings of bronchiectasis and the resulting individual patient scores showed that there was an excellent correlation between the observers (intraclass correlation coefficient of 0.85 and 0.81 for interobserver and intraobserver agreement, respectively). Conclusion: In the interpretation of HRCT findings of bronchiectasis, radiologist agreement appears to be fair. In our final analysis of the findings using the proposed score, we observed excellent interobserver and intraobserver agreement.